The Multi-GNSS Experiment (MGEX) of the International GNSS Service (IGS) – Achievements, prospects and challenges. Issue 7 (1st April 2017) - Montenbruck, Oliver; Steigenberger, Peter; Prange, Lars; Deng, Zhiguo; Zhao, Qile; Perosanz, Felix; Romero, Ignacio; Noll, Carey; Stürze, Andrea; Weber, Georg; Schmid, Ralf; MacLeod, Ken; et al.
Abstract: Over the past five years, the International GNSS Service (IGS) has made continuous efforts to extend its service from GPS and GLONASS to the variety of newly established global and regional navigation satellite systems. This report summarizes the achievements and progress made in this period by the IGS Multi-GNSS Experiment (MGEX). The status and tracking capabilities of the IGS monitoring station network are presented and the multi-GNSS products derived from this resource are discussed. The achieved performance is assessed and related to the current level of space segment and user equipment characterization. While the performance of orbit and clock products for BeiDou, Galileo, and QZSS still lags behind the legacy GPS and GLONASS products, continued progress has been made since launch of the MGEX project and already enables use of the new constellations for precise point positioning, atmospheric research and other applications. Directions for further research are identified to fully integrate the new constellations into routine GNSS processing. Furthermore, the active support of GNSS providers is encouraged to assist the scientific community in the generation of fully competitive products for the new constellations.